1996
DOI: 10.1183/09031936.96.09102064
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of PAF in postallergic propranolol-induced bronchoconstriction in guinea-pigs

Abstract: I In nv vo ol lv ve em me en nt t o of f P PA AF F i in n p po os st ta al ll le er rg gi ic c p pr ro op pr ra an no ol lo ol l--i in nd duWe conclude that platelet-activating factor may contribute to the development of propranolol-induced bronchoconstriction after allergic reaction in our guineapig model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…This is one of the most widely used techniques for determining airway constriction provoked by sensitizing antigen or chemical mediators in immunological and pharmacological studies using small experimental animals [8][9][10][11][12]. This method measures "ventilation-overflow (VO)", which is the volume of air which cannot enter into an animal's lung when the respirator inflates the lung ( fig.…”
Section: Determination Of Airway Constrictionmentioning
confidence: 99%
“…This is one of the most widely used techniques for determining airway constriction provoked by sensitizing antigen or chemical mediators in immunological and pharmacological studies using small experimental animals [8][9][10][11][12]. This method measures "ventilation-overflow (VO)", which is the volume of air which cannot enter into an animal's lung when the respirator inflates the lung ( fig.…”
Section: Determination Of Airway Constrictionmentioning
confidence: 99%
“…W e have show n that lipid mediators such as throm boxane A2, leukotrienes, and platelet activ ating factor are involved in PI B [11][12][13] , but sensory neuropeptides do not [ 14] , suggestin g an im portance of m ediator mechanism in our guinea pigs model. The present study w as conducted to elucidate the eÚ ects of bronchodilators on the PI B.…”
mentioning
confidence: 71%
“…The changes in lung resistance to in ation, de ned as the lateral pressure of the tracheal tube or pressure at the airway opening ( Pao [ cm H 2 O] ) w as measured using a pressure transducer ( M odel TP -603T, Nihon K oden Kogyo Co., L td., Tokyo, J apan) . Because we [ 15] demonstrated that the change in P ao following inhalation of leukotriene and histamine C 4 ( L TC 4 ) represented the average of the changes in pulm onary resistance and reciprocal dynam ic lung compliance, w e used change in the P ao as an overall index of the bronchial response to bronchoactiv e agents [11][12][13][14] .…”
Section: Preparation Of Animalsmentioning
confidence: 99%
“…As the change in the Pao, but not the absolute value of the Pao, represents the average of changes in the RL and 1/Cdyn when leukotriene C 4 is inhaled [17], we have used ch.anges in the Pao as an overall index of changes in airway calibre when oedema or inflammation of the lung parenchyma is negligible [9][10][11][17][18][19]. UNDW inhalation caused an acute and sharp increase in the Pao in the present study, suggesting the presence of bronchoconstriction but not airway oedema.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported a guinea-pig model of propranolol-induced bronchoconstriction [9], in which the inhalation of propranolol 20 min after antigen inhalation caused bronchoconstriction in passively sensitized guinea-pigs. Since specific inhibitors of thromboxane A 2 (TxA 2 ) [9] and platelet-activating factor (PAF) [10], but not sensory neuropeptides [11], significantly inhibited the propranolol-induced bronchoconstriction, we postulated that an allergic mediator mechanism was important in propranolol-induced bronchoconstriction.…”
mentioning
confidence: 99%